Memahami Pancasila Sebagai Bagian Tafsir Ajaran Islam: Dalil Teks Dan Konteks - Fathoni Fathoni; H.S. Tisnanta (Nizham Jurnal Studi Keislaman, 2018)
Understanding Pancasila as an open ideology, certainly can not be separated from the interpretation (hermeneutics/tafsir) in the text and context. When reading is interpreted as a physical process of scanning a line of words in the text by the sense of sight and digested by the brain, then understanding is the result of a set of reading processes to the text. There will always be a gap of understanding "intended" by both the author and the reader. This paper begins with the question: Why can Pancasila be categorized as part of Islamic interpretation (hermeneutics/tafsir)? Can Pancasila indoctrination use the Islamic approach? This paper uses philosophical methods and discourse analysis (language approach). Based on this method, it will get the art of understanding Pancasila as part of Islamic teachings to understand the text and its context. The research results shows that Pancasila is not contrary to the teachings of Islam, even the substance contained in the five principles of Pancasila are part of Islam itself. The indoctrination of Pancasila with an Islamic approach is relevant to be taken in the midst of a radicalism movement that is in the name of Islamic interests. There is a paradox between "accusations" that Islam is behind the radicalism movement against the Unitary Republic of Indonesia (NKRI) with the teachings of Islam itself that teaches that love of the homeland as a half of the faith (hubbul wathoni minal iman).